Iowa Birdline update, January 2, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for January 2, 1989. Highlights include Brant and Barrow's Goldeneye sightings, Glaucous and Thayer's Gull sightings, and the sighting of a Ferruginous Hawk. Includes summaries of Christmas Count sightings. Epson - sheet feed/flatbed